Targeting therapeutics to bone by conjugation with bisphosphonates. (June 2018) - Young, Robert N; Grynpas, Marc D
Graphical abstract: Highlights: PGE2 receptor EP4 agonists are anabolic in bones but retain some side effects. EP4 agonists conjugated with bisphosphonates target bones selectively. EP4 agonist-alendronate conjugates are effective bone anabolics when dosed weekly. Abstract : Bisphosphonates target and bind avidly to the mineral (hydroxyapatite) found in bone. This targeting ability has been exploited to design and prepare bisphosphonate conjugate prodrugs to deliver a wide variety of drug molecules selectively to bones. It is important that conjugates be stable in the blood stream and that conjugate that is not taken up by bone is eliminated rapidly. The prodrugs should release active drug at a rate appropriate so as to provide efficacy. Radiolabelling is the best method to quantify and evaluate pharmacokinetics, tissue distribution, bone uptake and release of the active drug(s). Recent reports have described bisphosphonate conjugates derived from the antiresorptive drug, alendronic acid and anabolic prostanoid drugs that effectively deliver prostaglandins and prostaglandin EP4 receptor agonists to bone and show enhanced anabolic efficacy and tolerability compared to the drugs alone. These conjugate drugs can be dosed infrequently (weekly or bimonthly) whereas the free drugs must be dosed daily.